Occupational and non-occupational risk factors for neck and lower back pain among computer workers: a cross-sectional study. Issue 4 (2nd October 2021) - Malińska, Marzena; Bugajska, Joanna; Bartuzi, Paweł
Abstract : Objectives. The aim of this study was to identify major determinants for neck and lower back pain (LBP) among office workers of different ages. Methods . Computer workers ( N = 2000) responded to a questionnaire on demographics, musculoskeletal disorders (MSDs), lifestyle characteristics, ergonomics of computer work and psychosocial and physical job characteristics. Results . Over 48% of respondents complained of MSDs last year, in particular neck pain and LBP. The results of logistic regression analysis revealed that prolonged computer time (odds ratio [ OR ] 1.92) and increased job demands ( OR 1.06) were likely to increase the risk of neck pain, while social support ( OR 0.96) and the use of seat-plate height adjustment ( OR 0.64) would help to reduce the risk. Risk factors for LBP included smoking more than 14 cigarettes a day ( OR 2.21), long hours spent working with a computer ( OR 1.94), increased physical exertion at work ( OR 1.29), increased work demands ( OR 1.03) and older age ( OR 1.03). Conclusions . The most effective way to eliminate MSD hazards in the workplace is to develop health programmes aimed at advocating healthy lifestyle behaviours and raising workers' awareness of workstation ergonomics and work organization, especially for women and older workers.